An Introduction to the Ethical Design, Conduct, and Analysis of Pediatric Clinical Trials - Yaster, Myron; Galinkin, Jeffrey; Schreiner, Mark S (Gregory's Pediatric Anesthesia, 2020)
This chapter provides an introduction to clinical trials and discusses the special problems of performing them in infants, children, and adolescents. It focuses on the prospective, randomized, blinded, placebo‐controlled trial as the accepted highest standard of evidence. Clinical trials rely on two processes to ensure their validity: masking (or blinding) of allocation assignment, and randomization. The chapter presents some of the ethical aspects of pediatric clinical trials. It details the operational planning and execution of pediatric clinical trials. As with any large‐scale project, a clinical trial has several stages that must be managed for the trial to be run and completed successfully. For most clinical trials, the stages include initial design, feasibility assessment, protocol development, data management and document preparation, subject recruitment/screening and enrollment, study treatment and follow‐up, close‐out and study termination, and an optional post‐trial follow‐up.